(untitled) (Italiano LinguaDue, 2023)
Understanding a written text involves not only making sense of its overtly expressed literal content, but also retrieving its subtly conveyed implied meanings by resorting to contextual clues. This process requires making pragmatic inferences. Previous studies have mainly focused on the processing of scalar implicatures in various populations, such as L2 learners, children, elders and individuals with Atypical Development. However, research on the inferential skills of L1 speakers and Typical Development (TD) young adults, and related to other kinds of implied meanings, is more limited. In this study we investigated the reading comprehension abilities of TD adults in the retrieval of various kinds of meanings in a written narrative text, both in L1 Italian and in L2 English. Adopting a between-subjects design, we administered an online questionnaire, in Italian and English versions, to Italian university students enrolled in various degree courses (54 participants per version). The questionnaire included a reading passage and multiple-choice comprehension items designed to assess the retrieval of 11 units of presupposed information, 4 units of entailed information, and 4 units of unstated content. Our findings partially diverged from previous research: a) the L2 speakers exhibited higher overall comprehension accuracy than L1 speakers; b) entailments were easier to retrieve than presuppositions or unstated information; and c) the L2 speakers’ performance did not appear to correlate with their proficiency level. We offer tentative explanations for these results: i) the students may have had more experience in comprehension tasks in their L2 or may have approached the questionnaire in the L2 with more attentiveness; ii) detecting entailments may be less challenging than other types of content since it involves recognising obvious reformulations of content; and iii) the levels of L2 proficiency were uneven across participants, or the participants’ self-reported L2 proficiency levels might not have accurately reflected the participants’ actual abilities, or at and intermediate/advanced proficiency level, the ability to retrieve meanings in text may be tied to cognitive factors that cut across language varieties. Abilità di lettura inferenziale dei giovani adulti - riconoscimento di contenuti impliciti e non dichiarati in italiano L1 e inglese L2 La comprensione di un testo scritto comporta non solo decifrarne il contenuto letterale, espresso esplicitamente, ma anche recuperarne i significati impliciti, veicolati indirettamente, ricorrendo a indizi contestuali. Questo processo necessita di inferenze pragmatiche. Studi precedenti si sono concentrati principalmente sull’elaborazione di implicazioni scalari in varie popolazioni, come gli apprendenti di L2, i bambini, gli anziani e gli individui a sviluppo atipico. Tuttavia, la ricerca sulle abilità inferenziali di parlanti di L1 e di giovani adulti a sviluppo tipico (TD), nonché relativa ad altri tipi di significati impliciti, è più limitata. In questo lavoro abbiamo indagato le capacità di comprensione di adulti TD nel recupero di vari tipi di significati in un testo narrativo scritto, sia in italiano L1 che in inglese L2. Impostando uno studio between-subjects, abbiamo somministrato un questionario online, in versione italiana e inglese, a studenti universitari italiani iscritti a vari corsi di laurea (54 partecipanti per versione). Il questionario comprendeva un brano di lettura e domande di comprensione a scelta multipla tese all’individuazione di 11 informazioni presupposte, 4 informazioni implicate logicamente e al riconoscimento di 4 informazioni non presenti nel testo. I risultati divergono parzialmente da quelli di ricerche precedenti: i parlanti di L2 hanno mostrato una comprensione complessiva più alta rispetto ai parlanti di L1; le implicazioni sono risultate più facili da recuperare rispetto alle presupposizioni o alle informazioni inespresse; e il grado di accuratezza delle risposte dei parlanti di L2 non sembra correlato al loro livello di competenza. I risultati ottenuti suggeriscono queste considerazioni: è possibile che gli studenti avessero maggiore esperienza nello svolgere compiti di comprensione nella L2 che non nella L1, o che abbiano affrontato il questionario nella L2 con maggiore attenzione; l’individuazione delle implicazioni potrebbe essere meno impegnativa rispetto ad altri tipi di contenuti, in quanto comporta il riconoscimento di ovvie riformulazioni dei contenuti; e i livelli di competenza nella L2 erano disomogenei tra i partecipanti, oppure non erano stati riportati accuratamente.